KEHARMONISAN KELUARGA PERKAWINAN BEDA AGAMA DI KOTA DAN KABUPATEN MALANG - Gumiri, Erik Rahman (El-Izdiwaj: Indonesian Journal of Civil and Islamic Family Law, 2020)
Marriage law of Indonesia not set expressly about interfaith marriage, be allowed or be forbidden. But beside that, there is other law who has set about interfaith marriage, that is the law of administration of population. In daily life, interfaith marriage still many happened and can not be avoided. As happened in the city and Malang regency, East Java.This research want to know how harmony family of interfaith marriage in the city and Malang regency. Purpose of this research is want to describe and analyze implementation of interfaith marriage in the city and Malang regency, describe and analyze how to responses of legal expert and practitioners, and describe and analyze how existence family of interfaith marriage in the city and Malang regency in hamony family perspective.This research is legal reseach, combination between normative legal research and emperical legal research. According to place, this reseach is field research. The approach using in this research is statute approach and case approach. Datas collection by interviews and documentations. Informan in this research is families interfaith marriage.Result of research found that, implementation of interfaith marriage in the city and Malang regency by two ways. First, by request decision to the district court. Second, by subduing themselves; where one of couple converting his religion. Responses of legal experts and practitioners about interfaith marriage in the city and Malang regency still different and become debate. There is allow according to Holy Qur’an, and also there is forbid according to regulations. While existence family of interfaith marriage in the city and Malang regency in hamony family perspective, according to their avowal, they are very harmony. Although they are have been married for decades, they are stay in a household together.